Pulmonary actinomycosis as a cause of chronic productive cough in a heavy smoker male with poor dental hygiene: A case report - Musaed Alsamawi (14778031) (2023)
Pulmonary actinomycosis is a rare chronic granulomatous bacterial disease caused by Actinomyces species. Given its nonspecific clinical and radiological manifestations, the diagnosis might be delayed or even missed. Pulmonary actinomycosis mimics tuberculosis, aspergillosis, or malignancy both clinically and radiographically, and it should be considered in patients with chronic lung diseases. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.6031